ANALISIS KELAYAKAN USAHATANI NANAS (Ananas comosus L.) POLA TANAM MONOKULTUR DI KECAMATAN PRINGGASELA - Unul Fikri; Rizal Ahmadi; Dwi Haryati Ningsih (Sosio Agri Papua, 2024)
The horticultural crop industry is very important for agricultural growth in Indonesia. Horticultural commodities such as pineapples can be developed to gain financial benefits. This research aims: 1) To determine the costs, revenues and income of pineapple farming with monoculture planting patterns in Pringgasela District, 2) The feasibility of pineapple farming with monoculture planting patterns in Pringgasela District. This research method is a descriptive method. The collection technique uses survey techniques. The location of this research was carried out in three villages, namely Jurit Village, Pringgasela Village and West Pengadangan Village, Pringgasela District, East Lombok Regency, chosen purposively. Determining respondents used quota sampling of 30 people. Data is analyzed using cost, revenue, income and R/C Ratio analysis. The conclusion of the research is that the average production cost of pineapple farming with a monoculture planting system in Pringgasela District is Rp46,618,450/LLG/planting season or Rp74,193,025/Ha/planting season, total revenue Rp30,788,083/LLG/planting season or Rp208,150,796/Ha/planting season, income earned is Rp84,169,633/LLG/planting season or Rp133,957,771/Ha/planting season, The Value of R/C ratio is 2.8, meaning that pineapple farming with a monoculture planting system in Pringgasela District is feasible